Anomalies of critical state in fracturing geophysical objects - Chmel, A.; Kuksenko, V. S.; Smirnov, V. S.; Tomilin, N. G. (CCSD, 2007)
International audience Non-linear time-sequences of fracture-related events were studied in drifting sea-ice and fracturing rock. A reversible drop of the b-value was detected prior to the large-scale sea-ice cover fragmentation, when the time sequence of impact interactions between ice-fields was fully decorrelated. A similar loss of the temporal invariance of the fracture process was revealed in the time sequence of microfracture events detected in a loaded rock sample. These temporal gaps in the continuous critical state of the considered self-organizing, open systems were attributed to the property of hierarchicity inherent in the geophysical objects. A combination of scaling and hierarchic features in the behavior of fracturing solids manifests itself in the heterogeneity of the temporal pattern of fracture process.